High incidence of ischemic stroke occurrence in irradiated lung cancer patients: a population-based surgical cohort study. - Shih-Kai Hung; Moon-Sing Lee; Wen-Yen Chiou; Ching-Chih Lee; Yi-Chun Chen; Chun-Liang Lai; Nai-Chuan Chien; Wen-Lin Hsu; Dai-Wei Liu; Yu-Chieh Su; Szu-Chi Li; Hung-Chih Lai; et al. (PLoS ONE, 2014)
Background and purpose A high risk of stroke occurrence has been reported in several types of irradiated cancer patients. However, clinical data are lacking in irradiated lung cancer patients. The present study intended to explore a risk level of ischemic stroke occurrence in irradiated lung cancer patients. Methods A nationwide population-based database obtained from the Taiwan National Health Insurance was analyzed. Between 2003 and 2006, we recruited 560 resected lung cancer patients into two study groups: surgery-plus-irradiation (n = 112) and surgery-alone (n = 448). Patients treated with chemotherapy were excluded. Propensity score match was used for pairing cases with a ratio of 1∶4. Two-year ischemic-stroke-free survival was defined as the primary endpoint. Results Three observations supported a high risk of ischemic stroke occurrence in patients with postoperative irradiation when compared with those patients with surgery alone: first, a high incidence per 1,000 person-year (22.3 versus 11.2, 1.99 folds); second, a low two-year ischemic-stroke-free survival rate (92.2% versus 98.1%, P = 0.019); and third, a high adjusted hazard ratio (HR, 4.19; 95% CI, 1.44-12.22; P = 0.009). More notably, the highest risk of ischemic stroke occurrence was found in irradiated patients who had diabetes mellitus (HR, 34.74; 95% CI, 6.35->100; P<0.0001). Conclusions A high incidence of ischemic stroke was observed in irradiated lung cancer patients, especially in those with diabetes mellitus. For these patients, close clinical surveillance and strict diabetes control should be considered. Further studies to define detail biological mechanisms are encouraged.